Synthesis of Diarylacetylenes Bearing Electron-Withdrawing Groups via the Smiles Rearrangement - Bujok, Robert; Mąkosza, Mieczysław (Synthesis, 2019)
Nitrobenzyl benzothiazol-2-yl sulfones and nitrobenzyl 1-phenyl-1H-tetrazol-5-yl sulfones react with chlorides of aromatic acids to form β-acyl derivatives. These products undergo the Smiles rearrangement resulting in the formation of the corresponding nitrophenyl arylacetylenes in 50–60% overall yields (approx. 75% per step). Sulfones bearing CF3 or CN groups instead of a NO2 substituent form mixtures of the acetylenes in moderate yields and benzyl aryl ketones in yields above 40%.
Keywords: acetylenes; sulfones; Smiles rearrangement; Julia–Kocienski olefination; benzyl ketones